Virtual preoperative planning and navigation in bone oncology - Ritacco, Lucas E.; Milano, Federico E.; Ayerza, Miguel A; Muscolo, Domingo L.; Farfalli, Germán L.; Aponte-Tinao, Luis A. (Revista del Hospital Italiano de Buenos Aires, 2013)
Virtual Preoperative Planning (VPP) and Intraoperative Virtual Navigation (IVN) are a set of technologies used to measure oncological margins in 3 dimensions (3D), locate small intraosseous tumors and apply controlled resections preserving anatomical structures. During VPP patient acquired multimodal images are processed and an interactive virtual scenario is created. An expert surgeon can use this platform to measure oncological distances and preplan osteotomies in safe areas. IVN is a procedure which allows the execution of the VPP with a mean error less than 3 mm. This set of technologies, called Computer Assisted Surgery (CAS), is a new tool for the surgeon that can perform complex surgical procedures in a predictable and safe way
Keywords: surgical navigation; bone tumor resection; computer aid surgery